COMPARATIVE MARKET ANALYSIS OF WORLD PRODUCTION AND INTERNATIONAL FRUIT TRADING - Živković, Dragić; Jelić, Sreten (Economics of Agriculture, 2009)
The objective was to analyse the properties of organisational and economic conditions known to be the principal business indices of an enterprise in order to show the impact on technical and technological segments of enterprise business activities. The ultimate goal was to make records on positive business trends expected to enhance future business activities.